Impacto de la heterogeneidad espacial del tráfico de red en el problema del apagado de celdas en redes ultra-densas. - Galeno-Brajones, Jesús; Luna-Valero, Francisco; Carmona Murillo, Javier; Valenzuela-Valdés, Juan Francisco; Zapata Cano, Pablo Helio (My University, 2023)
The ultra-dense deployment of small base stations is one of the enabling technologies for the next generation of mobile networks (5G and 6G), which leads to an increase in the energy consumption of the infrastructure. This work addresses the selective switch-off of these base stations as a multi-objective optimization problem and analyzes its impact on complexity compared to a network traffic distribution modeling with different levels of irregularity (severity of heterogeneity) in the location of the user equipment. Experimental analysis with three multi-objective metaheuristics on nine different scenarios shows that as the spatial modeling of traffic becomes more irregular, the search for solutions by the algorithms is affected and can alter their ranking, while both network capacity and energy consumption decrease.
Keywords: Internet; Telecomunicaciones; Redes ultra-densas; 5G; Tráfico de red; Metaheurísticas; Optimización multi-objetivo